Pengaruh Konflik Peran Ganda Dan Dukungan Sosial Terhadap Kinerja Tenaga Kesehatan Pada UPT Puskesmas Kopeta Maumere - Maria Viche Estorina Maring; Imanuel Wellem; Imelda Virgula Wisang (Program Studi Kewirausahaan Universitas Nusa Nipa Indonesia, 2025)
This study aimed to; (1) figure out the description of Health Worker Performance, Dual Role Conflict, and Social Support; (2) analyze the influence of Dual Role Conflict and Social Support on Health Workers' Performance both partially and simultaneously. The population in this study were health workers of UPT Puskesmas Kopeta Maumere, totaling 68 people. Because the population was limited, this research was conducted by census or saturated sampling. Data were collected through questionnaires and analyzed using descriptive and inferential statistical methods, namely multiple linear regression. Hypothesis testing was done through the F test and t-test. The results of descriptive analysis showed that the Health Worker Performance variable was in good criteria, the Dual Role Conflict variable was in good criteria, then the Social Support variable was in good criteria. The statistical results of the t-test showed that partially the Dual Role Conflict variable had a negative and significant effect on the Performance of Health Workers. Furthermore, the Social Support variable had a positive and significant effect on the Performance of Health Workers. The results of the F test statistics showed that simultaneously the Dual Role Conflict and Social Support variables had a significant effect on the Performance of Health Workers. The results of the determination analysis indicated that the two independent variables in this study were able to explain the variation in the rise and fall of the performance of UPT Puskesmas Kopeta Maumere Health Workers by 23.7%.